Shelf-life Determination of Fish Koya using Critical Moisture Content Approach: Shelf-life Determination of Fish Koya using Critical Moisture Content Approach - Anandito, R.B.K.; Siswanti; Purnamayati, Lukita; Sodiq, Hangga (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2017)
The objective of this study was to determine shelf-life of fish koya prepared from Snakehead Murrel [Channa striata Bloch, 1793)] and tempeh powder and packed in metalized plastic. Moisture adsorption isotherm of fish koya at 30 °C was determined by static gravimetric method over a wide range of water activity, i.e., from 0.113 to 0.843. The obtained moisture adsorption isotherm curve was expressed by employing Guggenheim-Anderson-de Boer equation. Accelerated shelf-life testing (ASLT) with critical moisture content approach was used to predict shelf-life of fish koya. The critical moisture content obtained by caking fish koya was 7.6 g H2O 100 g–1 solids. Koya stored at 30 oC with 75 %, 80 %, and 85 % of relative humidity (RH) had shelf-life of 234 d, 203 d, and 180 d, respectively.